Pancreatic panniculitis in systemic lupus erythematosus and Crohn's disease: rare event - Lucas N. Lessa e Silva; Miguel Augusto M. Pereira; Marcella F. Nunes; Enoï G. Vilar; Luciana Pantaleão (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Pancreatic panniculitis (PP) is a rare manifestation of pancreatic disease, involving subcutaneous adipose tissue. We report two cases of this entity: a 37-year-old female patient with systemic lupus erythematosus (SLE) and an elderly woman with Crohn's disease. These are two chronic autoimmune inflammatory diseases that can be uncommonly related to acute pancreatitis and that culminates in PP. We also provide a brief review of the treatment, diagnosis and morphology of the lesions, as well as the pathophysiology of the disease. The importance of histopathological analysis of lesion biopsies is highlighted as an important diagnostic tool.